2022
DOI: 10.1007/s10903-022-01424-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Area-Based Socioeconomic Measures with Tuberculosis Incidence in California

Abstract: We assessed the association of area-based socio-economic status (SES) measures with tuberculosis (TB) incidence in California. We used TB disease data for 2012–2016 (n = 9901), population estimates, and SES measures to calculate incidence rates, rate ratios, and 95% confidence intervals (95% CI) by SES and birth country. SES was measured by census tract and was categorized by quartiles for education, crowding, and the California Healthy Places Index (HPI)and by specific cutoffs for poverty. The lowest SES area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Language used at medical visit and at home were roughly concordant which provides an opportunity to use language at home when language at medical visit is not available. Non-English speaking persons could be at increased risk for TB compared with other persons from the same country because previous studies have shown non-U.S.-born persons with low educational attainment are at increased risk of TB and, from our analysis, we see non-U.S.-born persons with low educational attainment are more likely not to speak English [35,36].…”
Section: Plos Onementioning
confidence: 62%
See 1 more Smart Citation
“…Language used at medical visit and at home were roughly concordant which provides an opportunity to use language at home when language at medical visit is not available. Non-English speaking persons could be at increased risk for TB compared with other persons from the same country because previous studies have shown non-U.S.-born persons with low educational attainment are at increased risk of TB and, from our analysis, we see non-U.S.-born persons with low educational attainment are more likely not to speak English [35,36].…”
Section: Plos Onementioning
confidence: 62%
“…Among U.S.-born, 54% (CI: 52-55) reported very good or excellent health. Lower proportions of good or excellent health were reported by persons born in Mexico or in Vietnam: 26% (CI: 24-28) and 29% (CI: [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]). The highest proportion with very good or excellent health was among persons born in India at 62% (CI: 52-71).…”
Section: Overall Health and Risk Factors For Tb Reactivationmentioning
confidence: 99%
“…In addition, these two entities might share common causes that could lead to their occurrence. One significant example is the socioeconomic disadvantages some subjects may sustain that could fuel both the clinical condition of sarcopenia and a greater risk of infections such as TB, due to poor hygiene [36,37]. At the same time, the lack of a proper health education strategy could hinder our progress in both sarcopenia and TB's evolution and prognosis [38,39].…”
Section: Introductionmentioning
confidence: 99%